Diasporic homecomings to the Kurdistan region of Iraq: Pre- and post-return experiences shaping motivations to re-return. (October 2019) - Baser, Bahar; Toivanen, Mari
This article examines the dynamics of voluntary return migration to the Kurdistan region of Iraq in the post-Saddam period and provides a contextualised analysis of the returnees' experiences in a rapidly shifting geopolitical situation in Kurdistan. It specifically focuses on examining how diasporans' motivations to return, as well as their plans to re-return, are shaped in relation to their experiences in host societies and in the 'homeland'. Drawing from qualitative interviews, it shows that Kurdish diasporans' return can be characterised as 'diasporic homecoming' as it is motivated by the desire to contribute to the economic and political development of the Kurdistan region of Iraq. However, the mismatch between expectations and 'homeland' realities combined with positive experiences and social capital accumulated in the host country makes plans for re-return more foreseeable and less risky.